Proposta de reformulação do concurso para a obtenção ou renovação do título de enfermeiro estomaterapeuta - Thuler, Suely Rodrigues (2018)
SOBEST- Brazilian Association of Stomatherapy: stomas, wounds and incontinences, established in 2003, the title of TiSOBEST specialist in order to qualify stomatherapist nurses to practice the specialization, validate professional training and scientific-technical skills, by achievement of title awarding exams with pre-established criteria. The need felt by the Board to assess practical skills, prompted the present study. The study aims to propose an evaluation model that measures the skills in a wide range of this specialization. To reach these purposes, analysis include, the psychometric analysis of the level of difficulty; the discrimination and reliability coefficient of the items tested; the organization of Collection of Multiple Choice Items, after selection and adaptation, according to Criteria for Elaboration of Items, of the questions used in previous exams; reduction from one hundred items on the written exam, to eighty items and a presentation to the Board, proposal of addition of the Objective Structured Clinical Examination – OSCE to the two phases of the current exam, which nominated a commission to evaluate the cost, organization and operationalization of the reformulation of the title awarding exam